Land Use, Settlement, and Modern Landscapes - Romanova, Elena A. (International Journal of Economics and Financial Issues, 2015)
The paper summarizes main factors influencing the look of contemporary regional landscape, i.e. the system of land use management and settlement patterns that are organically shaped by the region's geological structure and terrain. The case in question – the Kaliningrad region – has seen its fair share of redrafting of administrative and state borders over the past century. Not only that: this territory, largely devoid of natural contrasts, has experienced dramatic shifts in economy, settlement systems, and ethnic composition of its population, - all of which is reflected in the way the regional landscape is presented today. Keywords: modern landscape; land use; settlement systems; landscape genesis JEL Classifications: J1; Q00; R1